Design and analysis of cantilever beam used Kevlar fiber composite for automobile applications. (2022) - Karthik, K.; Unnam, Neethish Kumar; Thamilarasan, J.; Kolappan, S.; Rameshkumar, R.
Abstract: Recent research focused on the structural application of composite materials. A dynamical analysis of the vibration of Kevlar fibre composite materials and deformation structures is carried out. The model analysis identifies the natural frequency ranges for composite materials and deformations. Natural frequency is provided the better results for automobile structural applications. The cantilever beam is drawn by the ANSYS workbench modular, and one end is fixed; another limitation is free. This condition is assumed when the applied force of composite beams at different mode behaviour was analysed. Six deformation shapes were revealed from the finite element investigations. Mode shapes of 1 to 6 predict the maximum levels of natural frequency and equivalent conditions. 25.27 strain rates are analysed from the dynamic characteristics of 17.80 Hz presented the natural frequency of this Kevlar fibre composite.